PENGARUH PELATIHAN TERHADAP KETERAMPILAN KADER DALAM PEMBUATAN PMT MODISCO DI WILAYAH KERJA PUSKESMAS PEMATANG PANJANG KECAMATAN AIR PUTIH KABUPATEN BATUBARA TAHUN 2012 - Faradhiba Sandi; Evawany Y Aritonang; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Modisco is Modified Dietetic Skim and Cotton Sheet Oil , composition consist of milk, margarine and sugar. That used to improve children’s weight quickly and it has been designed to anticipate any bad impact of nutritional status. To produce Modisco is easy and simple but there are many Posyandu cadres don’t have capability to make it. This study was quasy experimental , adopted one group Pre test and Post test design. The sample to this research involved all cadres whose serving and is being official to serve community on Pematang Panjang Health Center, noted 15 cadres. The objective of this research is to determine the influence of training against their knowledge and skill in producing self PMT Modisco. The training has been done in any workshop and display demo. In collecting the data, provided a questionnaire and by interview, while the data of skill by providing the draft list. Post Test was done twice immediately after training, the other test one week after training. In analyzing the data, using a paired sample t-test analysis method. The result of test showed that their knowledge and skill rose up after having training. According to the data analysis with paired sample t-test before and after traning indicated its rate of p =0.000, there is a significant influence between the training to their skill as Posyandu cadres in producing PMT Modisco. It is advised to cadres be proactive to improve knowledge and skill, every ability is encouraged to share especially to mother who have malnutrition child, and to encourage those cadres having good ability always socialize in producing PMT Modisco as an effort  prevent any malnutrition to public where the Helth Center serving. Keywords : Training,  Cadres Skill, PMT Modisco.